PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS, UKURAN, DAN AKTIVITAS PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2012-2014 - Putri Ismaida; Mulia Saputra (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The research examines the effect of growth of sales, profitability, size of firm, and activiy of firm on capital structure. The sample of this research was taken from property and real estate companies listed on Indonesia Stock Exchange at 2012-2014. The sample was taken using purposive sampling. The sample used was 126 companies. In order to test the hypothesis the statistical methods used was multiple linear regression analysis.       Partially the results of this research shows that profitability and size of firm have positive and significant influence on capital structure, whereas growth of sales and activity of firm have no significant effect on the dependent variable. Meanwhile in the simultaneous test, the four independent variables are seen to have significant influences to the capital structure. Keywords: Capital structure, growth of sales, profitability, size of firm, and activity of firm